Comparative results of subjective assessment by professional athletes of the functional state of the knee joint after anterior cruciate ligament repair with semitendinosus and gracillis tendons or peroneus longus tendon grafts - M. N. Velichko; A. U. Terskov; A. M. Belyakova; E. O. Hrabrova; A. V. Bodrov; A. V. Shturmin; A. S. Umnikov; A. A. Shurygina (National Electronic Information Consortium (NEICON), 2024)
Aim: to evaluate the subjective functional state of the knee joint in professional athletes after arthroscopic reconstruction of the anterior cruciate ligament depending on the type of the autograft.Materials and methods: the study included 37 professional athletes, divided into 2 groups. Athletes of the first group underwent arthroscopic ACL reconstruction using hamstring tendon autograft, i. e. semitendinosus and gracillis tendons (ST/GR group). Athletes of the second group underwent reconstruction using peroneus longus autograft (PL group). For subjective evaluation IKDC, Lysholm and Cincinnati questionnaires were used. The significance of differences was assessed using the Mann - Whitney test. Differences were considered significant at p < 0.05.Results: according to the Cincinnati questionnaire, the median scores of athletes from the ST/GR group was 96.0 points, from the PL group - 100.0 points (Me [Q1; Q3]: 96.0 [91.0; 100.0] and 100.0 [92.3; 100.0], respectively). According to the criteria of the rating scale, the median Lysholm score in points in the ST/GR group was 95.0, and in the PL group - 97.5 points (Me [Q1; Q3]: 95.0 [90.0;100.0] and 97.5 [92.0;100.0], respectively). According to IKDC measurements, the median score in the ST/GR group was 90.8, and in the PL group - 95.4 (Me [Q1; Q3]: 90.8 [81.0; 94.3] and 95.4 [89.1; 98.5], respectively.Conclusion: peroneus longus tendon autograft can be used for ACL reconstruction in professional athletes.